2009 39th IEEE Frontiers in Education Conference 2009
DOI: 10.1109/fie.2009.5350582
|View full text |Cite
|
Sign up to set email alerts
|

Computer Science and Computer Information Technology majors together: Analyzing factors impacting students' success in introductory programming

Abstract: In 2004 Northern Kentucky University began offering a Bachelor of Science degree in Computer Information Technology. As these new majors began to enroll alongside Computer Science majors in the required and standard Computer Science 1 (CS 1) course, the context of CS 1 shifted. Accordingly, we made curriculum changes to adapt the introductory programming sequence to this new context. These changes included: creating a "CS 0.5" preparatory programming course taught in a variety of languages; allowing the schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The following articles were analyzed: Alexander et al ( 2003 All articles were peer reviewed. The studies were published between 2003 and 2017 and most of them (8) were presented in a conference run by ACM or IEEE. The studies originated from 12 countries: the US (4), Canada (1), Jamaica (2), United Kingdom (2), Ireland (1), Spain (1), Sweden (1), Estonia (1), Russia (1), India (1) and Pakistan (1), and covered 3 continents, Northern America, Europe and Asia.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following articles were analyzed: Alexander et al ( 2003 All articles were peer reviewed. The studies were published between 2003 and 2017 and most of them (8) were presented in a conference run by ACM or IEEE. The studies originated from 12 countries: the US (4), Canada (1), Jamaica (2), United Kingdom (2), Ireland (1), Spain (1), Sweden (1), Estonia (1), Russia (1), India (1) and Pakistan (1), and covered 3 continents, Northern America, Europe and Asia.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Although mathematical skills are the most widely used factor in student selection in CS & IT, it has not proved to be as powerful a predictor of success as has been expected (e.g. [8,10,33]). Other skills investigated involve verbal skills in the language used in studies [28], previous programming experiences and sciences [3].…”
Section: Introductionmentioning
confidence: 99%
“…They found that female students who decided to enroll in the computer science program had more confidence in their ability to compete with males. Finally, a study by Doyle et al, (2009) evaluated student success in a CS course and examined factors contributing to their success. They concluded that neither gender nor major affected student success in the course.…”
Section: Hypothesesmentioning
confidence: 99%